2018
DOI: 10.1177/1524838018770414
|View full text |Cite
|
Sign up to set email alerts
|

Young People Who Display Harmful Sexual Behaviors and Their Families: A Qualitative Systematic Review of Their Experiences of Professional Interventions

Abstract: It is estimated that 30-50% of all childhood sexual abuse involves other young people as perpetrators. The treatment of harmful sexual behavior (HSB) in young people has evolved from interventions developed for use with adult perpetrators of sexual offenses. Increasingly, these approaches were not seen as appropriate for use with young people. The purpose of this qualitative systematic review was to establish what intervention components are viewed as acceptable or useful by young people and their families in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…While services are a crucial element in these young people's rehabilitation, and in their chance of living a normal life free of abusive behaviors, little is known about the experiences of young people with sexual behavior problems in tertiary services (Grady et al, 2018;Campbell, Booth, Hackett & Sutton, 2018). Grady et al (2018), for example, found that they could only identify five qualitative studies on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While services are a crucial element in these young people's rehabilitation, and in their chance of living a normal life free of abusive behaviors, little is known about the experiences of young people with sexual behavior problems in tertiary services (Grady et al, 2018;Campbell, Booth, Hackett & Sutton, 2018). Grady et al (2018), for example, found that they could only identify five qualitative studies on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…From the research that has been conducted, tertiary interventions appear to have a number of positive effects for these young people, such as increasing their sense of self-confidence and self-efficacy (Halse et al, 2012;Draper, Errington, Mar and Makhita, 2013). Many young people with sexual behavior issues appear to value interventions by tertiary services (though they may also be challenged by them), especially when these are undertaken with professionals who employ nonjudgemental approaches and avoid labelling (Campbell et al, 2018). The development of a positive therapeutic relationship is especially appreciated; these young people often struggle with emotional loneliness and lack social support (Grady et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also important to note that too much data can be overwhelming for some practitioners ( Munro, 2020 ). Another important advantage of the AIM3 is the broad assessment of HSB that it creates by taking into context multiple domains of a young person’s life and well-being, helping practitioners focus not only on the HSB itself ( Campbell et al, 2020 ; King-Hill, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recommending too much or too little intervention, restrictions, and restraints may be unethical and even harmful to minors in their ongoing development and maturation. Information, such as the ways children and adolescents report their own experiences during assessment and intervention, will be important ( Campbell et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the challenges, a growing number of scholars agree that learning about the life experiences and views of CSEY is crucial if we want to help them (Hampton & Lieggi, 2020). Understanding how service-users perceive the mechanisms that lead to positive outcomes is needed to design and deliver effective policies and interventions—particularly with regard to youth who display harmful sexual behaviors (Campbell et al, 2018). Accordingly, the present synthesis focuses on qualitative studies that contribute in-depth and nuanced understanding of help-seeking processes and help-related experiences of CSEY.…”
Section: Introductionmentioning
confidence: 99%